RECOMBINOGENESIS AND PRODUCTIVITY OF PENTAPLOID WHEAT HYBRIDS - L. P. Khlebova; N. V. Barysheva (Acta Biologica Sibirica, 2016)
The using of stable tetra derivatives created by hybridization of durum wheat with Triticum timopheevii Zhuk. and T. boeoticum Boiss. is one of the real possibilities to involve some genes of those species in breeding the cultivated hexaploid wheat. We carried out the cytological analysis as well as evaluation of the pollen and grain fertility of four hybrids obtained by crossing bread wheat samples with two resistant to stem and leaf rust durum wheat lines derived from T. timopheevii (HT-10) and T. boeoticum Boiss. (HB-11). Bread wheat served as a maternal parent. F1 hybrids were grown in the climate chamber and experimental field. It was found the frequencies of chiasma per cell were 24.93±0.14 and 25.10±0.09 in the field growing season and phytotron conditions, respectively. The average number of bivalents per cell varied from 13.86±0.03 to 13.96±0.02 regardless of both genotypes and growing conditions. It is shown the diploid part of nuclei in the 35-chromosome hybrids provides them with an enough buffer capacity and a certain indifference to behavior of univalents. More or less intensive elimination of single chromosomes did not affect significant the fertility of F1 plants. The average grain fertility was 54.35 and 53.63% under field and climate chamber growing conditions, respectively. Minor violations of the synapses of chromosomes in interspecific hybrids have revealed the resistance to pathogens has been transferred from T. timopheevii and T. boeoticum in durum wheat, most likely, by genetic recombinations. This fact allows us to consider the immune tetraploid forms as the primary gene pool for bread wheat and, thus, it creates a good prospect for further introgression of resistance to the rust fungi in T. aestivum L. commercial varieties.